A scientometric visualization analysis of the gut microbiota and gestational diabetes mellitus - Su, Zehao; Liu, Lina; Zhang, Jian; Guo, Jingjing; Wang, Guan; Zeng, Xiaoxi (Frontiers in Microbiology, 2025)
BackgroundThe prevalence of gestational diabetes mellitus (GDM), a condition that is widespread globally, is increasing. The relationship between the gut microbiota and GDM has been a subject of research for nearly two decades, yet there has been no bibliometric analysis of this correlation. This study aimed to use bibliometrics to explore the relationship between the gut microbiota and GDM, highlighting emerging trends and current research hotspots in this field.ResultsA total of 394 papers were included in the analysis. China emerged as the preeminent nation in terms of the number of publications on the subject, with 128 papers (32.49%), whereas the United States had the most significant impact, with 4,874 citations. The University of Queensland emerged as the most prolific institution, contributing 18 publications. Marloes Dekker Nitert was the most active author with 16 publications, and Omry Koren garnered the most citations, totaling 154. The journal Nutrients published the most studies (28 publications, 7.11%), whereas PLoS One was the most commonly co-cited journal, with a total of 805 citations. With respect to keywords, research focuses can be divided into 4 clusters, namely, “the interrelationship between the gut microbiota and pregnancy, childbirth,” “the relationship between adverse metabolic outcomes and GDM,” “the gut microbiota composition and metabolic mechanisms” and “microbiota and ecological imbalance.” Key areas of focus include the interactions between the gut microbiota and individuals with GDM, as well as the formation and inheritance of the gut microbiota. Increasing attention has been given to the impact of probiotic supplementation on metabolism and pregnancy outcomes in GDM patients. Moreover, ongoing research is exploring the potential of the gut microbiota as a biomarker for GDM. These topics represent both current and future directions in this field.ConclusionThis study provides a comprehensive knowledge map of the gut microbiota and GDM, highlights key research areas, and outlines potential future directions.